2020
DOI: 10.1016/j.bbih.2020.100048
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the gut-brain axis in a neurodevelopmental rodent model of schizophrenia

Abstract: Background Although the aetiology of schizophrenia remains unknown, it has been suggested that it might occur in response to alterations in the gut-brain axis (GBA), the bi-directional communication system between the gut and the brain. The current study aimed to determine whether the “two-hit” animal model of neuropsychopathology (maternal immune activation combined with adolescent cannabinoid exposure), produced abnormalities in the GBA Method Pregnant Wistar rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…MIA during pregnancy has reportedly caused an increase in mesencephalic dopaminergic neurons in the foetal brain, which is associated with excessive dopaminergic signaling in the midbrain area in SCZ ( Winter et al, 2009 ). Besides, in utero MIA precondition offspring exhibit, a triggered HPA-axis stress response when exposed to cannabinoids in adolescence and exhibit SCZ associated behavior in a sex-specific manner with a remarkable decline in Bifidobacterium longum gut abundance ( Katz-Barber et al, 2020 ). Exposure to viral or bacterial pathogens in-utero also has been reported to enhance the risk of developing SCZ.…”
Section: Altered Gut Microbiota Inflammation and Neurodevelopmental D...mentioning
confidence: 99%
“…MIA during pregnancy has reportedly caused an increase in mesencephalic dopaminergic neurons in the foetal brain, which is associated with excessive dopaminergic signaling in the midbrain area in SCZ ( Winter et al, 2009 ). Besides, in utero MIA precondition offspring exhibit, a triggered HPA-axis stress response when exposed to cannabinoids in adolescence and exhibit SCZ associated behavior in a sex-specific manner with a remarkable decline in Bifidobacterium longum gut abundance ( Katz-Barber et al, 2020 ). Exposure to viral or bacterial pathogens in-utero also has been reported to enhance the risk of developing SCZ.…”
Section: Altered Gut Microbiota Inflammation and Neurodevelopmental D...mentioning
confidence: 99%
“…MIA appears to induce dysregulation of the bi-directional gut-brain axis (GBA) in particular the gut microbiome and HPA axis. Pro-inflammatory cytokines can modulate the offspring’s HPA axis activity, in particular CRH-R1 expression shown in rodent environmental ‘two-hit’ insult models ( 94 ), or modify its neuroimmune function and gut microbial colonization ( 95 ). Many studies highlight the role of gut microbiome in health ( 96 ) and disease ( 97 ).…”
Section: Inflammation and Activation Of The Hpa Axismentioning
confidence: 99%
“…Additionally, the same study showed that adult MIA offspring displayed altered gut microbiota, with differential relative abundance between components of the gut microbiota, including Ruminococcaceae. Likewise, in Wistar rats, an animal model combining MIA with polyI:C and adolescent cannabinoid exposure demonstrated a sex-specific effect, with adolescent female offspring exhibiting decreased fecal levels of Bifidobacterium longum, measured using qPCR (Katz-Barber et al, 2020). While very promising, these aforementioned studies should be interpreted with caution, since recapitulating the complexity of SZ in an animal model is still a challenge, and each study has its own limitations.…”
Section: Discussionmentioning
confidence: 99%